(untitled) (Acta Polytechnica CTU Proceedings, 2017)
The paper is focused on measurement and analysis of dynamic effects on railway turnouts. Two same-type turnouts with different fastening elasticity were chosen. Attention was focused mainly on the crossing part of the turnout, where the highest dynamic impacts occur. The point of the paper is the assessment of influence of soft rail pads on spread of dynamic energy through the construction.